2008
DOI: 10.1163/157075608x383683
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the ants: selection of oviposition sites by two myrmecophilous butterfly species

Abstract: Obligate myrmecophilous butterfl y species, such as Maculinea teleius and M. nausithous that hibernate as caterpillar in nests of the ant species Myrmica scabrinodis and M. rubra respectively, have narrowly defi ned habitat requirements. One would expect that these butterfl ies are able to select for sites that meet all their requirements. Both butterfl y species occur in habitats where their initial larval resource, the host plant Sanguisorba offi cinalis , is abundant, while the ant nests are relatively less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 33 publications
(31 reference statements)
1
44
2
3
Order By: Relevance
“…However, a sampling design of that nature was unattainable for practical reasons, since, despite extensive efforts in the field, it proved impossible to find other release points with comparable resource densities and boundary shape within our study area. The behaviour of the P. teleius, including movements, is highly dependent on two critical resources; the larval foodplant S. officinalis and the Myrmica host ants (Maes et al 2004;Batáry et al 2007Batáry et al , 2009Wynhoff et al 2008;Van Langevelde and Wynhoff 2009). To make it possible to take into account the strong effect of a resource availability which is highly variable, several dozen replicates per boundary type would be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a sampling design of that nature was unattainable for practical reasons, since, despite extensive efforts in the field, it proved impossible to find other release points with comparable resource densities and boundary shape within our study area. The behaviour of the P. teleius, including movements, is highly dependent on two critical resources; the larval foodplant S. officinalis and the Myrmica host ants (Maes et al 2004;Batáry et al 2007Batáry et al , 2009Wynhoff et al 2008;Van Langevelde and Wynhoff 2009). To make it possible to take into account the strong effect of a resource availability which is highly variable, several dozen replicates per boundary type would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Having reached their fourth instar, the larvae drop to the ground and are taken by the workers of Myrmica ants to their nest, where they lead a parasitic life, feeding on ant brood (Thomas et al 1998). The host ants of P. teleius are several species of Myrmica: mostly M. scabrinodis, M. rubra and M. rugulosa (Thomas et al 1989;Wynhoff et al 2008;Witek et al 2010Witek et al , 2011. The study was carried out in the vast complex of wet meadows located in the Vistula River, west of the Kraków city centre (southern Poland; Fig.…”
Section: Study Species and Areamentioning
confidence: 99%
“…Caterpillars on these plants thus have hardly any chance of being found and adopted by a Myrmica ant. Earlier studies showed that the neighbouring agricultural land is virtually ant-free (Wynhoff et al 2008). Due to modern agricultural techniques, such as frequent ploughing, manure injection and heavy grazing by cattle, invading ant colonies have only little chance of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the suitability of a certain habitat patch is determined by the abundance of both the host plant and the specific host ants (Van Dyck et al 2000 (for P. alcon); Wynhoff et al 2008;Anton et al 2008;Dierks and Fischer 2009;Batáry et al 2009). In and around the nature reserve Moerputten, the density of ant nests is much lower than that of the host plants (Wynhoff et al 2008;Van Langevelde and Wynhoff 2009). On road verges, too, and in some other nature reserves, the host plant density is also high, whereas it is missing in the pastures and fields under agricultural use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation